2004
DOI: 10.1111/j.0742-2822.2004.04052.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tei Index: Methodology and Disease State Values

Abstract: Systolic and diastolic ventricular dysfunction frequently coexist. Both are important determinants of prognosis; consequently, a clinical measurement that assesses both systolic and diastolic function may be more useful than one that addresses only one aspect of ventricular function. Recently, a Doppler-derived index (referred to as the Tei index, or myocardial performance index) that combines systolic and diastolic time intervals has been developed to assess global cardiac function. 1 In this brief review we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 24 publications
1
44
2
2
Order By: Relevance
“…Short-axis M-mode echocardiography was performed and the following measurements were obtained as an average of at least three cardiac cycles: Left ventricular internal diameter at diastole and systole (LVIDd and LVIDs, respectively), posterior wall thickness at diastole and systole (PWTd and PWTs, respectively), interventricular septal thickness at diastole and systole (IVSd and IVSs, respectively), and fractional shortening (%FS) was calculated using the equation, FS = [(LVIDd−LVIDs)/LVIDd] X 100. Tei index was determined from left ventricular inflow and outflow Doppler recordings as previously described [28].…”
Section: Methodsmentioning
confidence: 99%
“…Short-axis M-mode echocardiography was performed and the following measurements were obtained as an average of at least three cardiac cycles: Left ventricular internal diameter at diastole and systole (LVIDd and LVIDs, respectively), posterior wall thickness at diastole and systole (PWTd and PWTs, respectively), interventricular septal thickness at diastole and systole (IVSd and IVSs, respectively), and fractional shortening (%FS) was calculated using the equation, FS = [(LVIDd−LVIDs)/LVIDd] X 100. Tei index was determined from left ventricular inflow and outflow Doppler recordings as previously described [28].…”
Section: Methodsmentioning
confidence: 99%
“…However, accurate echocardiographic evaluation of right ventricular function remains difficult and challenging by its complex structural geometry and contraction pattern [1]. The Doppler echocardiographically derived myocardial performance index, also referred to as the Tei index, is easily obtainable and has been clinically useful in assessing global ventricular function in both, left and right ventricles, and adults and children [2][3][4]. The index combines systolic and diastolic time intervals and is independent of heart rate and ventricular geometry [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the inability to measure the interval between the end and onset of mitral inflow and the ejection time simultaneously is a limitation of conventional Tei index. 15,16 Tissue Doppler imaging (TDI) is a new ultrasound technique that selectively calculates and displays online myocardial velocity information derived from the Doppler shifts created by cardiac motion. 17 Studies that use Tei index derived from TDI demonstrated that TDI Tei index correlated with conventional Tei index very well.…”
Section: Introductionmentioning
confidence: 99%